Anionic polymerization of 1, 3-pentadiene in toluene: homopolymer, alternating and block copolymers. Issue 57 (25th May 2016) - Ren, Lei; Liu, Kun; He, Qing; Ou, Encai; Lu, Yanbing; Xu, Weijian
Abstract : Well-defined alternating and amphiphilic diblock copolymers containing poly(1, 3-pentadiene) were synthesized in toluene via living anionic polymerization. Abstract : The anionic polymerization of ( E )-1, 3-pentadiene (EP) and ( Z )-1, 3-pentadiene (ZP) was performed in aromatic solvent using n -butyllithium as initiator. In contrast to poly(ZP)s, the resulting poly(EP)s possessed the predicted molecular weights and narrow molecular weight distributions ( Đ ≤ 1.15). However, THF as polar additive has proved its validity to reduce the molecular weight distribution of poly(ZP) from 1.55 to as low as 1.16. The 1 H NMR and 13 C NMR results indicated that both poly(EP) and poly(ZP) consist of 1, 4-addition & 1, 2-addition units, without 3, 4-addition units. Moreover, a novel, well-defined styrene–pentadiene alternating copolymer has been synthesized in toluene via living anionic copolymerization and the NMR spectra demonstrated that the resulting copolymers obtained possess a strictly alternating structure and much narrower polydispersity ( Đ ≤ 1.17). Finally, the living nature of the polymerization was also inspected via sequential copolymerization with methyl methacrylate (MMA) and 2-vinylpyridine (2VP) to yield well-controlled diblock copolymers (poly(EP)- b -poly(MMA) & poly(EP)- b -poly(2VP)).